THE INFLUENCE OF DIGITAL MARKETING AND DIGITAL PAYMENT ON PURCHASE DECISION AT WOMEN FASHION STORE IN MTC MANADO - Umboh, Christina Natalia Stevhia; Tulung, Joy; Gunawan, Emilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to analyze the influence of digital marketing and digital payment on consumer purchasing decisions. Digital marketing includes various marketing strategies through digital platforms such as social media that aim to increase interaction with consumers. Meanwhile, digital payment includes various electronic payment methods that facilitate transactions between consumers and sellers, such as E-wallet. This research methodology uses a quantitative approach with data collection through questionnaires distributed to 100 consumers who have purchased women's clothing at MTC Manado. Data analysis was carried out using multiple linear regression to determine the effect of each independent variable (digital marketing and digital payment) on the dependent variable (purchase decision).  The results of the study show that digital marketing has a positive and significant influence on purchasing decisions, which means that an effective digital marketing strategy can increase consumer interest and trust in making purchases. Digital payment was also found to have a positive and significant influence on purchasing decisions, where the ease and security of the digital payment process encourage consumers to make transactions.   Keywords: Digital Marketing, Digital Payment, Purchase Decision